(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2022)
The objective of this research was to analyze the use of agricultural by-products (cassava and rice husks) for compost as an alternative for economic valuation. The applied methodology contemplated a completely randomized bifactorial design to determine the effects of the two research factors (proportions of by-products and composting systems) in six treatments; the physical variables analyzed were: temperature, pH and electrical conductivity (EC). The results revealed that treatments 5 and 6 showed higher temperatures in the initial phases of composting; however, upon reaching maturation, the temperature dropped to 21°C. The pH showed a very similar pattern in all treatments with a range from 5 to 9. A heterogeneous distribution of EC was observed in the final phase of composting; with values from 5.65 dS/m (T6) to 0.38 dS/m (T2). The by-products analyzed have great potential as raw material for compost.